(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2011)
The aim of the study was to determine the concentration of serum Ca, Mg, Cu, Fe, Zn and Mn in Bangladeshi conversion disorder patients compared to control subjects and to correlate the changes, if any, with different socio-demographic factors and nutritional status. Forty five conversion disorder patients were randomly recruited. Forty five healthy control subjects were also recruited by matching the socio-demographic status to that of the patients. Blood samples were analyzed to determine the concentration of serum Ca, Mg, Cu, Fe, Zn and Mn using atomic absorption spectroscopy. Except for Mg, the concentrations of the other elements (Cu, Fe, Zn, Ca, and Mn) decreased in patients compared to control, but the changes were not statistically significant (p > 0.05). Serum Mg level increased insignificantly in patients (p > 0.05). No significant relationship was found between the sociodemographic variables and serum Ca, Mg, Cu, Zn and Mn levels, except for serum Fe, where a significant negative correlation was found between serum Fe level and BMI (r = –0.428; p = 0.023). Key words: Conversion disorder patients; serum elements; socio-economic status DOI: http://dx.doi.org/10.3329/dujps.v9i2.7896 Dhaka Univ. J. Pharm. Sci. 9(2): 119-124, 2010 (December)